Development of interactive learning media using smart apps creator on electrical system of light vehicles in vocational high schools - Sofyan Al Farouqi; Hadromi; Dwi Widjanarko (JMEL : Journal of Mechanical Engineering Learning, 2025)
This study aims to develop and evaluate the feasibility and effectiveness of interactive learning media based on Smart Apps Creator (SAC) for the topic of lighting and signaling systems in light vehicles, intended for Grade XI students of the Light Vehicle Engineering Program at SMK Negeri 2 Salatiga. The background of this research stems from low student achievement and the limited use of engaging instructional media at SMK N 2 Salatiga, which has resulted in students having difficulty understanding the electrical system material. This study employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The developed media underwent validation by subject matter experts and media experts, receiving "highly feasible" ratings with feasibility percentages of 90.25% from the media expert and 88% from the subject matter expert. The effectiveness was tested through pretest and posttest evaluations analyzed using the N-Gain test. The N-Gain score from 34 students yielded an average of 0.324, which falls into the "moderate" category. It can thus be concluded that the learning media based on Smart Apps Creator provided to students is moderately effective in improving their learning outcomes.